2023
DOI: 10.3390/agronomy13092261
|View full text |Cite
|
Sign up to set email alerts
|

Storage Temperature and Grain Moisture Effects on Market and End Use Properties of Red Lentil

Bhawana Bhattarai,
Cassandra K. Walker,
Ashley J. Wallace
et al.

Abstract: Storing lentil is a strategy used by growers to manage price volatility. However, studies investigating the impact of storage conditions on the market and end use properties of lentil are limited. This study examined the effects of storage temperature (4, 15, 25, and 35 °C) and grain moisture (10 and 14%, w/w) on traits related to market (seed coat colour), viability (germination capacity), and end use properties (hydration capacity, milling efficiency, and cooking quality) in four red lentil cultivars (PBA Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In this study, grain samples from two contrasting red lentil cultivars (PBA Hallmark and PBA Jumbo2) were obtained from a previous study [7]. Both cultivars were stored under a factorial combination of two moisture contents (10 and 14%, w/w) and two contrasting temperatures of 4 and 35 • C for 360 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, grain samples from two contrasting red lentil cultivars (PBA Hallmark and PBA Jumbo2) were obtained from a previous study [7]. Both cultivars were stored under a factorial combination of two moisture contents (10 and 14%, w/w) and two contrasting temperatures of 4 and 35 • C for 360 days.…”
Section: Methodsmentioning
confidence: 99%
“…In current cultivars, it has been shown that the colour of the lentil seed coat is unstable and subject to change over time based on storage conditions and length of storage, shifting from a bright light to a duller or darker shade [6]. Previous research has identified the seed coat of red lentil changes to a deep brown colour when stored at or above 25 • C and under high grain moisture content (14%, w/w) [7]. Changes in seed coat colour in pulse grains have been linked to a reduction in bioactive compounds such as phenolic compounds in faba beans [8] and green lentil [6] subjected to extended storage periods.…”
Section: Introductionmentioning
confidence: 99%
“…The seed coat colour of lentil is an economic determinant for growers and traders as it strongly influences the marketability and value of the grain. The colour of the seed coat darkens over time particularly under extreme storage conditions and is primarily attributed to environmental factors such as temperature and grain moisture content [1]. Depending on the lentil grain moisture content and temperature at harvest as well as external weather conditions such as seasonal and daily variation in temperature during storage, the lentil seed coat can substantially darken.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the lentil grain moisture content and temperature at harvest as well as external weather conditions such as seasonal and daily variation in temperature during storage, the lentil seed coat can substantially darken. This can result in reduced marketability, the downgrading of the stored grain and, consequently, lower profits for growers [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation